Industrialization in Taiwan, 1946 - 72 : - Lin, Ching-yuan (Praeger Publishers, 1973)
The problems of the Taiwan economy in the late 1940s; policy incentives for the period of inward-oriented growth; Economic situation in the mid-1950s and the ensuing policy changes...